Integrating notational and positional analysis to investigate tactical behavior in offensive and defensive phases of football matches - Praça, G. M.; Moreira, P. E. D.; Andrade, A. G. P. de; Clemente, F. M.; Oliveira, W. B. de; Demétrio, G. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Most literature has neglected the possible influence of game phase - offensive and defensive - on players` and teams` behaviors measured by positional data. Also, the combined effect of contextual variables - match period, match venue, and match outcome - and game phases has not been investigated yet. Therefore, this study aimed to integrate notational and positional analysis to investigate individual and collective tactical behavior in different game phases (offensive and defensive) in football matches under different contextual conditions. The sample comprised 18 matches played by 24 U-20 elite Brazilian athletes during the 2021 national championship. The authors designed a notational system to classify the start and the end of the offensive phase (and consequently, the defensive phase of the opposing team). The positional data was gathered through global positioning system devices and manually integrated with the notational analysis. Contextual variables comprised match period (first vs second halves), match venue (home vs away matches), and match outcome (win vs draw versus lose matches). Results showed significant differences between game phases, with a more spread tactical positioning observed in the offensive phase. Furthermore, interactions between contextual variables and the game phase were observed, although the game phase presented the highest impact on the dependent variables. We conclude that a more spread tactical positioning characterizes offensive behavior and that the impact of the game phase was higher than contextual variables on tactical behavior, which emphasizes the need for future studies to split positional data into attacking and defensive ones. Also, integrating notational and positional analysis are a viable alternative to enrich the data interpretation of football matches concerning the influence of game phases on players` and teams` behaviors.